2018
DOI: 10.1016/j.pmcj.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive monitoring system for e-health smart homes

Abstract: Existing e-health monitoring systems mainly operate in isolation from the requirements of modern healthcare institutions. They do not include optimized techniques which learn the patient's behavior for predicting future important changes. We propose a new context-aware e-health monitoring system targeted at the elderly and isolated persons living alone. It monitors daily living activities and evaluates dependency based on geriatric scales used by health professionals. Its adaptive framework collects only relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
46
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 39 publications
1
46
0
2
Order By: Relevance
“…Issues in ongoing research have been extensively discussed, with initial solutions suggested in [ 4 ]. Context-aware approaches have been proposed previously; for example, [ 5 ]. However, only one [ 6 ] focused on crowd abnormality monitor and mitigation with the use of individual AR.…”
Section: Introductionmentioning
confidence: 99%
“…Issues in ongoing research have been extensively discussed, with initial solutions suggested in [ 4 ]. Context-aware approaches have been proposed previously; for example, [ 5 ]. However, only one [ 6 ] focused on crowd abnormality monitor and mitigation with the use of individual AR.…”
Section: Introductionmentioning
confidence: 99%
“…The retrieved data may indicate some deviations from the norm in the behavior of the household members. Information can be processed in terms of behavior analysis [ 8 , 9 , 10 ]. There are also very interesting research on sensing technologies for robotics which can assist elderly people in daily routine [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…For the health care systems, this is considered as a big challenge [8], these health care systems need to deal with the health issues of the elderly population [3,[5][6][7][9][10][11][12][13][14][15][16]. In order to develop effective health systems, they must be able to deal with the so-called "four giants" of geriatrics (Isaacs) as: instability, immobility, intellectual impairment and incontinence.…”
Section: Introductionmentioning
confidence: 99%